Impact of BGREI programme on rice productivity and farmers’ income of Odisha - Behera, R K; Mishra, S K; Awasthi, H K; Mondal, B; Das, Lipi (ORYZA-An International Journal of Rice, 2018)
The present study was conducted during the year 2016-17 in Mayurbhanj and Bargarh districts of Odisha state to assess the impact of Bringing Green Revolution to Eastern India (BGREI) programme on productivity and income of rice growers in Odisha. Two blocks from each district were selected, in such a way that one block in each district had more BGREI implemented villages and another one had less BGREI implemented villages. From each selected block, 02 BGREI-implemented villages and 02 distantly located non-BGREI-implemented villages were selected for investigation. Total 160 farmers (80 beneficiaries+ 80 non-beneficiaries) were selected as respondents for the study. The data were collected with the help of well-structured interview schedule through personal interview. The study revealed that after participation in the BGREI programme, the productivity of rice cultivated by the beneficiaries in the selected districts was increased from 32.47 q/ha to 49.17 q/ha. i.e. an increase of 51.43 per cent in rice productivity. Beneficiaries had 18.66 q higher productivity of rice as compared to the non-beneficiaries. The annual income of beneficiary farmers in the selected districts was also increased from Rs.1,20,514 to Rs.1,86,107 i.e. an increase of 54.43 per cent. Beneficiaries had Rs.74, 370 higher annual income as compared to the non-beneficiaries. B:C ratio of the beneficiaries increased from 1.51 to 2.68 i.e. an increase of 77.48 per cent. B:C ratio of Rice cultivation done by the beneficiaries was 1.58 times higher than the non-beneficiaries. So, BGREI programme is a farmer friendly programme and it should continue to sustain and improve the livelihood of farmers.